Changes of thermostability, organic solvent, and pH stability in Geobacillus zalihae HT1 and its mutant by calcium ion - Siti Nor Hasmah I,; Masomian, Malihe *; Nor Hafizah AK,; Mohd Shukri MA,; Leow, Thean Chor; Raja Noor Zaliha, R. A. R. (MDPI, 2019)
Thermostable T1 lipase from Geobacillus zalihae has been crystallized using counter-diffusion method under space and Earth conditions. The comparison of the three-dimensional structures from both crystallized proteins show differences in the formation of hydrogen bond and ion interactions. Hydrogen bond and ion interaction are important in the stabilization of protein structure towards extreme temperature and organic solvents. In this study, the differences of hydrogen bond interactions at position Asp43, Thr118, Glu250, and Asn304 and ion interaction at position Glu226 was chosen to imitate space-grown crystal structure, and the impact of these combined interactions in T1 lipase-mutated structure was studied. Using space-grown T1 lipase structure as a reference, subsequent simultaneous mutation D43E, T118N, E226D, E250L, and N304E was performed on recombinant wild-type T1 lipase (wt-HT1) to generate a quintuple mutant term as 5M mutant lipase. This mutant lipase shared similar characteristics to its wild-type in terms of optimal pH and temperature. The stability of mutant 5M lipase improved significantly in acidic and alkaline pH as compared to wt-HT1. 5M lipase was highly stable in organic solvents such as dimethyl sulfoxide (DMSO), methanol, and n-hexane compared to wt-HT1. Both wild-type and mutant lipases were found highly activated in calcium as compared to other metal ions due to the presence of calcium-binding site for thermostability. The presence of calcium prolonged the half-life of mutant 5M and wt-HT1, and at the same time increased their melting temperature (Tm). The melting temperature of 5M and wt-HT1 lipases increased at 8.4 and 12.1 ◦C, respectively, in the presence of calcium as compared to those without. Calcium enhanced the stability of mutant 5M in 25% (v/v) DMSO, n-hexane, and n-heptane. The lipase activity of wt-HT1 also increased in 25% (v/v) ethanol, methanol, acetonitrile, n-hexane, and n-heptane in the presence of calcium. The current study Int. J. Mol. Sci. 2019, 20, 2561; doi:10.3390/ijms20102561 www.mdpi.com/journal/ijms Int. J. Mol. Sci. 2019, 20, 2561 2 of 22 showed that the accumulation of amino acid substitutions D43E, T118N, E226D, E250L, and N304E produced highly stable T1 mutant when hydrolyzing oil in selected organic solvents such as DMSO, n-hexane, and n-heptane. It is also believed that calcium ion plays important role in regulating lipase thermostability